Peran Kepala Sekolah dalam Pengembangan Pendidikan Karakter Nasionalis - Ridholina Ridholina; Noor Miyono; Ngurah Ayu Nyoman Murniati (Journal Prakarsa Paedagogia, 2022)
The purpose of the  study is to describe the principal  as a  manager and as a leader in the  development of district education This research uses qualitative descriptive methods.  The subjects of  the study were the Principal, vice principal, teachers, staff and students. Data collected through interviews, observations, and documentations.  The principal is the controller for school resources, especially teachers and school employees.  The results of this study show that the success of character development in  schools cannot be separated from the  role of  the principal.  So great is the role of the principal in the process of achieving educational goals, that it can be said that the success or failure of a school is largely determined by the quality of the principal, especially in his ability to empower teachers and employees in the direction of a conducive working atmosphere. The principal has a role and responsibility as an office manager, including predicting the future of the school, for example about the quality desired by the community, innovating by taking initiatives and creative activities for the progress of the school, creating strategies or policies to succeed these innovative thoughts, compiling plans, both strategic planning and operational planning, finding educational resources  and providing educational facilities, controlling or controlling the implementation of education and its results.  As a manager, the   principal must be able to manage the development character programs   properly, starting from planning, organizing, directing and controlling .  As a leader,    the principal  must be have to set  an example for all school members, and be able to mobilize all school members to carry out  character development  activities